PEMANFAATAN VIDEO SAMPAH PLASTIK TERINTEGRASI PADA PEMBELAJARAN IPS UNTUK MENGEMBANGKAN KESADARAN LINGKUNGAN BAGI SISWA DI SEKOLAH DASAR INPRES 1 KAYUMALUE PAJEKO - Elvira, Elvira; Misnah, Misnah; Ratu, Bau (STKIP PGRI Situbondo, 2024)
This research aims to implement the use of plastic waste videos as a social studies learning media to enhance the environmental awareness competence of fifth-grade students at Inpres 1 Kayumalue Pajeko Elementary School. The research subjects consist of 16 students. The method employed is Classroom Action Research with a spiral model, and both cycles utilize Project-Based Learning. Based on the research results, the researcher and the partner teacher have successfully designed and implemented the learning model effectively over two cycles, addressing any challenges encountered. The research findings illustrate a significant increase in the average scores of students' environmental awareness competence. In the first cycle, the average score was 69.06, categorized as